A Combination of Visudyne and a Lipid‐anchored Liposomal Formulation of Benzoporphyrin Derivative Enhances Photodynamic Therapy Efficacy in a 3D Model for Ovarian Cancer1. (7th January 2019) - Rizvi, Imran; Nath, Shubhankar; Obaid, Girgis; Ruhi, Mustafa Kemal; Moore, Kaitlin; Bano, Shazia; Kessel, David; Hasan, Tayyaba
Abstract: A major objective in developing new treatment approaches for lethal tumors is to reduce toxicity to normal tissues while maintaining therapeutic efficacy. Photodynamic therapy (PDT) provides a mechanistically distinct approach to treat tumors without the systemic toxicity of chemotherapy drugs. PDT involves the light‐based activation of a small molecule, a photosensitizer (PS), to generate reactive molecular species (RMS) that are toxic to target tissue. Depending on the PS localization, various cellular and subcellular components can be targeted, causing selective photodamage. It has been shown that targeted lysosomal photodamage followed by, or simultaneous with, mitochondrial photodamage using two different PS results in a considerable enhancement in PDT efficacy. Here, two liposomal formulations of benzoporphyrin derivative (BPD): (1) Visudyne (clinically approved) and (2) an in‐house formulation entrapping a lipid conjugate of BPD are used in combination with direct PS localization to mitochondria, endoplasmic reticulum and lysosomes, enabling simultaneous photodamage to all three organelles using a single wavelength of light. Building on findings by our group, and others, this study demonstrates, for the first time in a 3D model for ovarian cancer, that BPD‐mediated photodestruction of lysosomes and mitochondria/ER significantly enhances PDT efficacy at lower light doses than treatment with either PS formulation alone. Abstract : A combination of Visudyne and a lipid‐anchored liposomal formulation of benzoporphyrin derivative enhances photodynamic therapy efficacy.